EVALUASI USABILITY SISTEM INFORMASI MONITORING GRADE GULA A DAN B DI PT ANDALAN FURNINDO MENGGUNAKAN SYSTEM USABILITY SCALE (SUS) - Ibrahim Ufuk (PT. Hasba Edukasi Mandiri, 2025)
Information systems play an essential role in improving the efficiency and effectiveness of company operations, particularly in monitoring product quality. This study aims to evaluate the usability level of the Grade A and B Sugar Monitoring Information System at PT Andalan Furnindo using the System Usability Scale (SUS) method. The research was conducted through a survey involving 30 respondents from various departments that utilize the system. Data were analyzed descriptively using SPSS software to obtain the average SUS score, normality test, and reliability test. The results indicate an average SUS score of 85.17, which falls into the Excellent category, with a Cronbach’s Alpha value of 0.852, demonstrating high instrument reliability. These findings show that the information system has a very good level of usability and supports user productivity. However, several technical issues were identified, such as data input speed and information access delays, which require optimization. Recommended improvements include enhancing system performance, simplifying the user interface, and providing regular user training.